Fuel properties and chemical compositions of the tar produced from a 5 MW industrial biomass gasification power generation plant. Issue 2 (May 2015) - Li, Liang; Huang, Sheng; Wu, Shiyong; Wu, Youqing; Gao, Jinsheng; Gu, Junwen; Qin, Xiaogang
Abstract The industrial biomass gasification tar (IBGT) was analyzed for its basic fuel properties and chemical compositions. The results suggested that IBGT had some special properties (high water content, high ash content, high viscosity, etc.). IBGT was subjected to extraction to obtain n-hexane soluble, n-hexane insoluble/toluene soluble, toluene insoluble/tetrahydrofuran soluble, and tetrahydrofuran insoluble fractions, which were characterized by FTIR. The n-hexane soluble fraction was further fractionated by column chromatography into four fractions, which were characterized by gas chromatography-mass spectrometry (GC/MS). The n-hexane insoluble/toluene soluble and toluene insoluble/tetrahydrofuran soluble fractions were characterized by 1H NMR. The results showed that the first fraction (6.96 wt.%) contained alkanes and alkenes; the second fraction (15.68 wt.%) contained 1–3 ring aromatics; the third fraction (29.20 wt.%) contained oxygen compounds, such as phenols; the fourth fraction (6.40 wt.%) contained nitrogen compounds, such as quinoline, isoquinoline, amine and amide; the fifth fraction (21.07 wt.%) mainly contained polycyclic aromatic structure with short aliphatic side chain and long aliphatic bridge bond; the sixth fraction (12.32 wt.%) mainly contained polycyclic aromatic structure with heteroatom side chain; the seventh fraction (8.38 wt.%) contained ash, coke and unreacted biomass. These results may present an effective solution to utilization of IBGT.